Universal access in human-computer interaction. methods, technologies, and users : 12th International Conference, UAHCI 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings /: methods, technologies, and users : 12th International Conference, UAHCI 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. Part I : (2018) - Unknown
No abstract available